Analisis Perancangan Alat Kerja untuk Menghindari Musculoskeletal Disorders Menggunakan Metode Rapid Entire Body Assessment (REBA) di CV Rama Teknik - Fahrudin, Wakhit Ahmad; Candra, Adi; Zulziar, Marjuki (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2024)
an Research analysis was carried out on designing work tools to avoid musculoskeletal disorders using the Rapid Whole Body Assessment (REBA) method at CV Rama Teknik. Data was collected through asking questions during interviews, and filling out the Nordic Body Map (NBM) questionnaire to ascertain which parts of the body experienced discomfort which could cause a certain level of musculoskeletal disorders. The posture conditions of assembly process workers that can cause musculoskeletal disorders are sitting work posture and standing work posture. The results of the Pick Test observations showed that the frequency of the slouched sitting position was 41 times with a percentage of 46% and the frequency of the upright sitting position was 49 times with a percentage of 54%. The results of the Nordic Body Map questionnaire indicate that the risk level for workers' MSDs is "medium" with an individual score level of 62 for worker 1, 62 for worker 2, and 58 for worker 3. In accordance with the risk level classification based on the total individual score with a score level of 50-70, it is at “medium” risk level. The REBA calculation result for the standing work posture for the first worker is 3, the second worker is 2, and the third worker is 2, so the risk level for the standing work posture for all assemblers is "low", while the REBA calculation result for the sitting work posture for the first worker is 5 , the second assembler is 6, and the third worker is 6, then the risk level for sitting work posture is "medium", according to the REBA risk level if the score is 4-7 then the risk level is "medium". Keywords: Ergonomics Work Design, REBA, Teaching Aids